2019
DOI: 10.3389/fpsyg.2019.02298
|View full text |Cite
|
Sign up to set email alerts
|

(Why) Do You Like Scary Movies? A Review of the Empirical Research on Psychological Responses to Horror Films

Abstract: Why do we watch and like horror films? Despite a century of horror film making and entertainment, little research has examined the human motivation to watch fictional horror and how horror film influences individuals’ behavioral, cognitive, and emotional responses. This review provides the first synthesis of the empirical literature on the psychology of horror film using multi-disciplinary research from psychology, psychotherapy, communication studies, development studies, clinical psychology, and media studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 169 publications
(210 reference statements)
5
43
0
5
Order By: Relevance
“…Men have been found to engage in more dangerous forms of behavior (Tamás et al, 2019), and thus they may have become more habituated to frightening phenomena relative to women. Also in line with previous research (Hoffner & Levine, 2005; Martin, 2019), which has consistently found that men report higher liking of frightening entertainment, we found that men reported more enjoyment than women in a recreational horror setting. This finding may reflect a preference among men for engaging in thrill-seeking behavior and frightening and violent leisure activities (Martin, 2019), although other research has suggested that gender differences are reduced and in some studies nonsignificant when neutral measures, such as need for affect, are administered (Bartsch, Appel, & Storch, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Men have been found to engage in more dangerous forms of behavior (Tamás et al, 2019), and thus they may have become more habituated to frightening phenomena relative to women. Also in line with previous research (Hoffner & Levine, 2005; Martin, 2019), which has consistently found that men report higher liking of frightening entertainment, we found that men reported more enjoyment than women in a recreational horror setting. This finding may reflect a preference among men for engaging in thrill-seeking behavior and frightening and violent leisure activities (Martin, 2019), although other research has suggested that gender differences are reduced and in some studies nonsignificant when neutral measures, such as need for affect, are administered (Bartsch, Appel, & Storch, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our results demonstrate gender differences, with women reporting higher fear and lower enjoyment compared with men. Lower reported fear among men is not surprising in light of previous studies on horror (for a review, see Martin, 2019) and may be due to social desirability or past experience with frightening situations as part of stereotypical forms of play and entertainment. Men have been found to engage in more dangerous forms of behavior (Tamás et al, 2019), and thus they may have become more habituated to frightening phenomena relative to women.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, sensation-seeking is tied to a desire for greater arousal and associated with enjoyment of horror media (though the latter relationship is somewhat inconsistent. For review, see Martin, 2019 ). However, it is unclear how sensation seeking would lead to increased positive resilience or preparedness for a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most consistent personality correlates of horror fandom is sensation seeking (Martin 2019). Sensation seeking may be described as a tendency to seek out experiences that maximize arousal through novelty, complexity, or intense sensations (Zuckerman, 1994).…”
Section: Personality and Horrormentioning
confidence: 99%